STUDY TO INVESTIGATE INDUCED SPAWING METHOD AND LARVAL REARING OF THE SEA CUCUMBER Holothuria scabra *) - Retno Hartati; Delianis Pringgenies (JOURNAL OF COASTAL DEVELOPMENT, 1998)
In irder to increase natural population stocks, a sea cucumber cultivation project was attempted in the Karimunjawa Islands (Java Sea, Indonesia). Since continuous production of larvae is essential to such a project, this portion of the research focuses on methods of inducing the sea cucumber Holothuria scabra to spawn and monitoring the development of resulting larvae. Four different types of environmental manipulation were used to try and induce spawning; artificial fertilization (using manually extracted eggs and sperm), thermal shock (raising the temperature of the spawning medium), desiccation (partially drying out) and treatment with potassium chloride (KCL) solutions of various concentrations. The development of the resulting larvae was carefully observed. Results indicate that thermal shock, desiccation and potassium chloride (KCL) are all effective in stimulating the sea cucumber Holothuria nobilis to spawn. Thermal shock gave the best result with both male and female spawning and 90% larvae development. Using a stocking density of 300 larvae/ liter in 10 liter aquaria, larvae was successfully raised up to pentactula stage. Regardless of the method used to induce spawning, fertilizer eggs development into auricularia larvae at 31 hours and 30 minutes. These larvae then metamorphosed into doliolaria and pentactula larvae at day 13 and 26. Mortality of all stocks at the pentactula stage was probably due to lack of provision of settlement substance.